2012
DOI: 10.1542/peds.2011-1601
|View full text |Cite
|
Sign up to set email alerts
|

Six Developmental Trajectories Characterize Children With Autism

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Autism is widely considered a heterogeneous disorder in terms of etiology and phenotype. Although autism is usually a lifelong disorder, little is known about the rate or timing of how children develop regarding their communication and social functioning. WHAT THIS STUDY ADDS:Utilizing annual evaluations for a large population of children with autism, we describe the 6 most common trajectories from diagnosis through age 14 years. Trajectories revealed considerable variation, and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
212
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(235 citation statements)
references
References 36 publications
12
212
1
5
Order By: Relevance
“…Understanding the developmental course of ASD is crucially important for managing life care and planning treatment. However, ASD occurs with many varied developmental paths (Fountain et al 2012;Lord et al 2015), and there is no one consistent life outcome (Fein et al 2013;Helles et al 2015;Steinhausen et al 2016). Variation in ASD developmental course has ranged from typical development in infancy that becomes atypical in early childhood, to marked infant impairment in social and cognitive skills that changes to become optimal adaptive functioning in adulthood (Anderson et al 2014;Fein et al 2013;Fountain et al 2012;Helles et al 2015;Howlin et al 2013;Levy and Perry 2011;Lord et al 2015;Yirmiya and Charman 2010).…”
Section: Do Shared Features Provide Construct Validity For An Asd Spementioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the developmental course of ASD is crucially important for managing life care and planning treatment. However, ASD occurs with many varied developmental paths (Fountain et al 2012;Lord et al 2015), and there is no one consistent life outcome (Fein et al 2013;Helles et al 2015;Steinhausen et al 2016). Variation in ASD developmental course has ranged from typical development in infancy that becomes atypical in early childhood, to marked infant impairment in social and cognitive skills that changes to become optimal adaptive functioning in adulthood (Anderson et al 2014;Fein et al 2013;Fountain et al 2012;Helles et al 2015;Howlin et al 2013;Levy and Perry 2011;Lord et al 2015;Yirmiya and Charman 2010).…”
Section: Do Shared Features Provide Construct Validity For An Asd Spementioning
confidence: 99%
“…The only broadly successful ASD treatment has been early behavioral intervention programs (Kasari 2015;Schreibman et al 2015;Smith and Iadarola 2015;), but these treatments are not unique to ASD (Losinski et al 2014), and the long-term effectiveness of these programs is not yet known (Fernell et al 2011. Researchers who studied infant siblings of children with ASD concluded no single early behavior could predict ASD diagnoses (Zwaigenbaum et al 2015), and ASD has been found with widely varied trajectories of development (Fountain et al 2012;Lord et al 2015) and varied life outcomes (Fein et al 2013;Helles et al 2015;Steinhausen et al 2016). …”
mentioning
confidence: 99%
“…Although children with medical homes have fewer unmet needs, 27 gaps in both health 28 and education 29 still exist and are associated with poorer outcomes. 30,31 Future research should examine whether certain conditions are more likely to be associated with different trajectories 11,12 and, taking a life course approach, whether the timing or age at which SHCN are experienced also influence outcomes, over and above the pattern of the longitudinal profile. It will also be important to clarify the extent to which the risk and protective factors identified in conceptual models, such as those presented by O'Connor et al 32 and Newacheck et al, 13,14 explain differences in children's outcomes based on their longitudinal SHCN profile.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 There is currently limited knowledge about the natural history and variability over time of SHCN as a broad grouping and about how outcomes may vary by differing trajectories (eg, emerging, persistent), if such exist. 11 Newacheck et al 13,14 and, more recently, Bethell et al 15 have argued that this missing longitudinal information is crucial to inform the planning of medical, developmental, and education support services for these children across their life course.…”
mentioning
confidence: 99%
“…4 These data were linked to the BMF using probabilistic matching (for details on the linkage, see King and Bearman 2011) and include each child's date of first evaluation at the DDS as well as five items that measure social and three items that measure communication functioning. We use an equally weighted index of these sets of items to construct age-adjusted social and communication severity scores for each child measured on scales ranging from 1 to 100 (for details on the construction and distributions of the developmental functioning scores, see Fountain, Winter, and Bearman 2012). We consider children with scores below 25 at first DDS evaluation to be low functioning.…”
Section: Datamentioning
confidence: 99%